Cadar Wanita Dalam Perspektif Al-Qur’an - Fithrotin, Fithrotin (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2017)
The issue of women's veils is a hot conversation among socialists, not just recently ladies who veiled reap the pros and cons. Since the first classical clerics even among friends have different opinions related to women's clothing in general, and the obligation of women covering his face in particular. The dispute between friends and clerics departed from the al-ahzab 59 and Nur 31 which the provisions of the matter and the law are uncertain (mutasyabihat), still have various possibilities of law and tasyri 'attitudes, let alone the difference reinforced by the second source of law, namely the Hadith of the Prophet. The commentators can not be one-way in establishing women's veil law in shari'ah. This research is a literature (library research) with the method of presenting descriptive analysis that attempts to describe the concept contained in the Qur'an by describing the meaning contained by the verses studied and then compared with the phenomena that occur in the Society. The result of the research concludes that the review of the argument that reinforces the opinion of jumhur, ja'iz legal decision is very appropriate, because if the veil must be done by women because it can cause slander and lust even men also have the same law, namely hurus keep himself from immoral and air lust by all means.